2018
DOI: 10.1002/ijgo.12481
|View full text |Cite
|
Sign up to set email alerts
|

Association between induced abortion history and later in vitro fertilization outcomes

Abstract: A history of induced abortion was associated with worse IVF outcomes, especially a history of more than two surgical abortions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
2
8
2
Order By: Relevance
“…In contrast to our findings, two published studies 34,35 reported that a history of TOP led to worse pregnancy outcome following IVF. However, certain key parameters that are closely related to reproductive outcome, such as embryo quality and the embryo's developmental stage, were not taken into consideration in those studies 34,35 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our findings, two published studies 34,35 reported that a history of TOP led to worse pregnancy outcome following IVF. However, certain key parameters that are closely related to reproductive outcome, such as embryo quality and the embryo's developmental stage, were not taken into consideration in those studies 34,35 .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our findings, two published studies 34,35 reported that a history of TOP led to worse pregnancy outcome following IVF. However, certain key parameters that are closely related to reproductive outcome, such as embryo quality and the embryo's developmental stage, were not taken into consideration in those studies 34,35 . Moreover, varying definitions of the control group and inconsistency in the potential confounders considered may also explain the contradictory results between studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of the present research also showed that the odds of female infertility increased by 0.94 for each abortion (P = 0.004), this is consistent with the findings of the study by Cong et al (3). In another study, a history of induced abortion was associated with worse IVF outcomes, especially a history of more than 2 surgical abortions (19).…”
Section: Discussionmentioning
confidence: 93%
“…Our results have shown that women who underwent surgical evacuation had thinner EMT than those who did not. Although it had a wide range of applications, the surgical evacuation, which could lead to the altering secretion of inflammatory cytokines and the thinning of endometrium, was usually considered as a damage factor of endometrium in the previous study [18]. A retrospective study found that surgical evacuation was revealed as a cause for endometrial thinning in miscarriage [13].…”
Section: Discussionmentioning
confidence: 99%
“…And there were some studies showed that endometrium thickness was associated with pregnancy outcomes [16, 17]. However, the influence of surgical evacuation on pregnancy outcome remains controversial [18, 19].…”
Section: Introductionmentioning
confidence: 99%